From autism to eating disorders and more: the role of oxytocin in neuropsychiatric disorders - Romano, Adele; Tempesta, Bianca; Micioni Di Bonaventura, Maria Vittoria; Gaetani, Silvana (Frontiers in Neuroscience, 2016)
Oxytocin (oxy) is a pituitary neuropeptide hormone synthesized from the paraventricular and supraoptic nuclei within the hypothalamus. Like other neuropeptides, oxy can modulate a wide range of neurotransmitter and neuromodulator activities. Additionally, through the neurohypophysis, oxy is secreted into the systemic circulation to act as a hormone, thereby influencing several body functions. Oxy plays a pivotal role in parturition, milk let-down and maternal behavior and has been demonstrated to be important in the formation of pair bonding between mother and infants as well as in mating pairs. Furthermore, oxy has been proven to play a key role in the regulation of several behaviors associated with neuropsychiatric disorders, including social interactions, social memory response to social stimuli, decision-making in the context of social interactions, feeding behavior, emotional reactivity, etc. An increasing body of evidence suggests that deregulations of the oxytocinergic system might be involved in the pathophysiology of certain neuropsychiatric disorders such as autism, eating disorders, schizophrenia, mood, and anxiety disorders. The potential use of oxy in these mental health disorders is attracting growing interest since numerous beneficial properties are ascribed to this neuropeptide. The present manuscript will review the existing findings on the role played by oxy in a variety of distinct physiological and behavioral functions (Figure 1) and on its role and impact in different psychiatric disorders. The aim of this review is to highlight the need of further investigations on this target that might contribute to the development of novel more efficacious therapies. Figure 1 Oxytocin regulatory control of different and complex processes.